CMR-Verified Myocardial Fibrosis Is Associated With Subclinical Diastolic Dysfunction in Primary Aldosteronism Patients - Zhou, Fangli; Wu, Tao; Wang, Wei; Cheng, Wei; Wan, Shuang; Tian, Haoming; Chen, Tao; Sun, Jiayu; Ren, Yan (Frontiers in Endocrinology, 2021)
Abstract Objectives: The main cardiac features of primary aldosteronism (PA) are impaired left ventricular (LV) diastolic function, and some articles also reported more cardiac fibrosis in PA patients. However, the correlation between LV dysfunction and diffuse myocardial fibrosis in PA remains unknown. Methods: We enrolled 84 PA patients and 28 essential hypertension (EH) patients in West China Hospital. Cardiac magnetic resonance imaging (CMR) contrast enhancement was arranged for all subjects. Postcontrast T1 time and left ventricular myocardial strains and strain rates were measured. Results: 76 PA patients and 27 essential hypertension (EH) patients were included in the final analysis. Blood pressure, LV mass indexes, and LV ejection fractions were comparable in both groups, while the global circumferential peak diastolic strain rate (PDSR) was lower (0.9 ± 0.3 vs. 1.1 ± 0.4, p<0.01) and the postcontrast T1 time was shorter (520 ± 38 vs. 538 ± 27, p=0.01) in PA patients than those in EH patients. Postcontrast T1 time (p=0.01) was independently related to global circumferential PDSR after adjusting for age and duration of hypertension in PA patients. Furthermore, plasma aldosterone concentration was negatively associated with postcontrast T1 time (R=-0.253, p=0.028) in PA patients. Conclusions: The global circumferential PDSR derived by CMR is decreased, and the diffuse myocardial fibrosis is increased in PA patients compared to those in blood pressure matched EH patients. The severity of cardiac diastolic dysfunction independently relates to the degree of diffuse myocardial fibrosis in PA patients, and the diffuse myocardial fibrosis may be caused by high PAC level. URL: http://www.chictr.org.cn/listbycreater.asp Trial registration number: ChiCTR2000031792.